Fast algorithm for VQ-based wavelet coding system - Khalifa, Othman Omran (2003)
The increasing demand of multimedia computing has led to the demand of using digital images. The manipulation, storage and transmission of these images in their raw form is very expensive, it significantly slows the transmission and makes storage costly. In this paper, a modified version of (Linde-Buzo-Gray)LBG algorithm using Partial Search Partial Distortion (PSPD) is presented for coding the wavelet coefficients. The proposed scheme can save 70 - 80 % of the Vector Quantization (VQ) encoding time compared to fully search VQ and reduced arithmetic complexity with out sacrificing performance.